THE CORRELATION BETWEEN HEREDITY AND MASS MEDIA EXPOSURE FACTORS ON THE EARLY MENARCHE INCIDENT ON ADOLESCENT GIRLS - Agrini Yesiska Tamo; Wahyul Anis; Budi Presetyo (Universitas Airlangga, 2022)
Menarche is the first menstruation that occurs in young women. The normal age is 12-14 years, but now there’s a tendency to decrease to younger age. The purpose of this study was to analyze the correlation of heredity and mass media exposure factors with the incidence of early menarche in adolescent girls at SMPN 56 Surabaya. The study used an observational analytic design with a cross-sectional approach. The sample of this research was adolescent girls of 7th-8th grade of SMPN 56 Surabaya and mothers, taken using simple random sampling method. The instrument was a questionnaire distributed online. The research data analyzed using the Chi-square test. The results showed that 39.13% adolescent girls who experienced early menarche had mothers who had a history of early menarche. The mass media exposure with a light level was 15.21% experienced premature menarche, while 84.78% experienced early menarche. The results of the Chi-square correlation test analysis between heredity and the incidence of early menarche in young girls stated that there was no relationship between the two variables with p = 0.068. The results of Chi-square analysis between the mass media exposure factors and the incidence of early menarche in young women obtained p value = 0.030, which can be concluded that there is a relationship between the two variables. The study concluded that there is a relationship between exposure to mass media and the incidence of menarche in young women so that supervision of adolescent girls is needed in accessing information in the mass media.